2012
DOI: 10.1111/j.1875-595x.2012.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Decline in dental caries among 12-year-old children in Brazil, 1980–2005

Abstract: Data showed a significant decrease in dental caries across the entire country, with an average reduction of 25% occurring every 5 years. General trends indicated that a reduction in DMFT index values occurred over time, that a further reduction in DMFT index values occurred when a municipality fluoridated its water supply, and mean DMFT index values were lower in larger than in smaller municipalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
(16 reference statements)
2
20
0
8
Order By: Relevance
“…In Brazil, studies by Bönecker et al [2002Bönecker et al [ , 2010 reported significant reductions in dental caries in preschool children from 1995 to 1999 and 1997 to 2008, respectively; however, the explanations for the trend were not clear. Narvai et al [2006] reported a 62% decline in DMFT from 1980 to 2003 and related the decline to expansion in the coverage by water fluoridation and increased use of fluoridated toothpaste, as stressed in other studies [Cury et al, 2004;Lauris et al, 2012]. However, they based their arguments on the plausibility of these 'historical facts' rather than on empirical evidence [Cury et al, 2004].…”
mentioning
confidence: 75%
“…In Brazil, studies by Bönecker et al [2002Bönecker et al [ , 2010 reported significant reductions in dental caries in preschool children from 1995 to 1999 and 1997 to 2008, respectively; however, the explanations for the trend were not clear. Narvai et al [2006] reported a 62% decline in DMFT from 1980 to 2003 and related the decline to expansion in the coverage by water fluoridation and increased use of fluoridated toothpaste, as stressed in other studies [Cury et al, 2004;Lauris et al, 2012]. However, they based their arguments on the plausibility of these 'historical facts' rather than on empirical evidence [Cury et al, 2004].…”
mentioning
confidence: 75%
“…12 But, yet, there remains a section of young population from developed as well as developing countries who present as high caries risk subjects. 3 It is not very uncommon to see young patients with multiple grossly decayed anterior as well as posterior primary teeth.…”
Section: Introductionmentioning
confidence: 99%
“…[123] A previous study has reported prevalence of as high as 92.11% among 9 year old and a mean dynamical mean field theory of 4.61 ± 3.14, higher than World Health Organization (WHO) goal for Healthy people (2000). [3] This worrisome prevalence and severity was attributed to lack of use of fluoride toothpaste (80%), lack of knowledge about the etiology of dental caries (98%) and ≥5 sugar exposures/day (30%).…”
Section: Introductionmentioning
confidence: 99%